SOCIAL PRACTICE ANALYSIS OF SINGLE-USE PLASTICS (SUPs) UTILIZATION IN CAFES AND RESTAURANTS : A CASE STUDY OF BANDA ACEH CITY - Aiyub, Cut Nurul Syifa; Haikal, Muhammad; Alkindy, Muhammad Aslam; Irhamna, Siti (Indonesian Journal of Environmental Sustainability, 2026)
Single-use plastics (SUPs) remain widely used in cafés and restaurants in Banda Aceh because they are perceived as practical, hygienic, and cost-efficient, despite their environmental impacts. This study examined the factors sustaining SUP use, the relationship between environmental awareness and behavior among business owners and consumers, and strategies for reducing reliance on SUPs. A qualitative descriptive approach was applied through field observations and in-depth interviews with 48 respondents, comprising 24 café and restaurant owners or managers and 24 consumers. Interview and observational data were coded and analyzed using NVivo within the framework of Social Practice Theory. The findings show that SUPs is influenced by product availability, convenience, perceived cleanliness, operational costs, consumer habits, inadequate washing facilities, limited access to environmentally preferable alternatives, and weak policy implementation. Although respondents generally understood the environmental consequences of SUPs, this awareness did not consistently translate into behavioral change, particularly among café owners and consumers. Reducing SUPs therefore requires coordinated interventions, including environmental education, business-level standard operating procedures, incentives for reusable alternatives, improved infrastructure, and stronger local regulations. These measures can support more sustainable consumption practices in Banda Aceh’s food-service sector.